Congenital thrombocytopenia with nephritis – The first case of MYH9 related disorder in Serbia - Kuzmanović, Miloš; Kunishima, Shinji; Putnik, Jovana; Stajić, Nataša; Paripović, Aleksandra; Bogdanović, Radovan (Vojnosanitetski pregled, 2014)
Introduction. The group of autosomal dominant disorders – Epstein syndrome, Sebastian syndrome, Fechthner syndrome and May-Hegglin anomaly – are characterised by thrombocytopenia with giant platelets, inclusion bodies in granulocytes and variable levels of deafness, disturbances of vision and renal function impairment. A common genetic background of these disorders are mutations in MYH9 gene, coding for the nonmuscle myosin heavy chain IIA. Differential diagnosis is important for the adequate treatment strategy. The aim of this case report was to present a patient with MYH9 disorder in Serbia. Case report. A 16-year-old boy was referred to our hospital with the diagnosis of resistant immune thrombocytopenia for splenectomy. Thrombocytopenia was incidentally discovered at the age of five. The treatment with corticosteroids on several occasions was unsuccessful. Although the platelet count was below 10 × 109/L, there were no bleeding symptoms. Besides thrombocytopenia with giant platelets, on admission the patient also suffered sensorineuronal hearing loss and proteinuria. The diagnosis was confirmed with immunofluorescence and genetic analyses. Conclusion. Early recognition of MYH9-related diseases is essential to avoid unnecessary and potentially harmful treatments for misdiagnosed immune thrombocytopenia, and also for timely and proper therapy in attempt to delay end-stage renal failure and improve quality of life.